2016
DOI: 10.1259/bjr.20150998
|View full text |Cite
|
Sign up to set email alerts
|

First-line diagnosis of paediatric pneumonia in emergency: lung ultrasound (LUS) in addition to chest-X-ray (CXR) and its role in follow-up

Abstract: The effective role of LUS in the diagnosis and follow-up of lung consolidations and pleural effusions in paediatric patients in an emergency setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 27 publications
2
61
0
Order By: Relevance
“…From this set of articles, 99 (12.6%) abstracts were identified for further analysis based on PRISMA analysis (Figure ). QUADAS review was applied to the 99 articles and 12 (1.5%) (Table ) were selected for inclusion in the meta‐analysis based on inclusion criteria, data collection, and lack of bias. All studies were observational.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From this set of articles, 99 (12.6%) abstracts were identified for further analysis based on PRISMA analysis (Figure ). QUADAS review was applied to the 99 articles and 12 (1.5%) (Table ) were selected for inclusion in the meta‐analysis based on inclusion criteria, data collection, and lack of bias. All studies were observational.…”
Section: Resultsmentioning
confidence: 99%
“…Computed tomography (CT) of the chest is considered the radiologic gold standard in diagnosing pCAP, but its considerable radiation exposure and expense makes it unfeasible for routine use in the evaluation of pCAP . In this setting, provider‐performed point‐of care lung ultrasound (LUS) to diagnose pediatric pneumonia has shown promising results yielding significant accuracy compared with CXR . It is a portable, radiation‐free, and repeatable imaging method ideal for the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caiulo et al also reported an improvement (between the 3rd and 6th day) expressed in decrease in size or disappearance of subpleural consolidations in LUS (76 of 83) with clinical improvement and drop in inflammatory laboratory markers. Ianniello et al highlighted that LUS after 5 days showed a complete disappearance or decrease in size of subpleural pulmonary parenchymal lesions in 84.6% of their patients. Omran et al reported the complete regression or diminished size in 81.6% of patients on day 5 of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, they reported improvement of symptoms with decreases in the size of the lung consolidations. Ianniello et al 33 performed follow-up lung US examinations to monitor small consolidations and small pleural effusions, which are not detected by chest radiography. After 5 days of treatment, the lung US showed a complete disappearance or a decrease in the size of consolidation patches in 84.6% of their patients, and 15% showed disease stability or an insubstantial decrease in size.…”
Section: Discussionmentioning
confidence: 99%